Rethinking the Tactile Paving Installation System Based on the City Rhythm of Visually Impaired Pedestrians in Urban Networks - Fadhlillah, Fariz (Universitas Diponegoro, Indonesia, 2024)
This study was conducted in Bandung, the provincial capital of West Java, to reevaluate the tactile paving installation system based on the movement patterns of visually impaired pedestrians in urban networks. Given the rising global prevalence of low vision and blindness, creating inclusive urban environments has become a critical health and social issue. The research aimed to address the gap in accessibility by focusing on how tactile paving can better align with the daily rhythms and needs of visually impaired individuals. Data collection involved interviews, and data analysis utilized a mixed-methods approach. Findings revealed that the movement patterns of visually impaired pedestrians are intricately connected to their essential activities. The study concludes that a hierarchical approach to tactile paving installation can improve efficiency, particularly in cities with limited funding, thus promoting broader and more effective development of inclusive urban networks. These insights are valuable for both immediate facility improvements and future transit-oriented development planning.